How do Elementary Students Perceive the Utility of Dual-Language Children’s Books? An Exploratory Study in French Immersion - Thibeault, Joël; Matheson, Ian A. (Language and Literacy / Langue et littératie, 2021)
Dual-language children’s books—books in which two languages cohabit—are currently gaining traction in the field of language education. Though some studies have zeroed in on the benefits of using them in classrooms, less is known about how learners perceive this tool’s utility for reading and language development. In this paper, we thus aim to explore how elementary students in French immersion perceive the utility of two types of dual-language books: translated, where all passages in French also appear in English, and integrated, where the story is told using an embedded discourse composed of both English and French.